Ethnicity and attitudes to deceased kidney donation: a survey in Barbados and comparison with Black Caribbean people in the United Kingdom - Seed Paul T; Adams O Peter; Morgan Myfanwy; Jones Roger (BMC, 2010)
Abstract Background Black minority ethnic groups in the UK have relatively low rates of deceased donation and report a higher prevalence of beliefs that are regarded as barriers to donation. However there is little data from migrants' countries of origin. This paper examines community attitudes to deceased kidney donation in Barbados and compares the findings with a survey conducted in a disadvantaged multi-ethnic area of south London. Methods Questionnaires were administered at four public health centres in Barbados and at three private general practices. Adjusted odds ratios were calculated to compare attitudinal responses with a prior survey of 328 Caribbean and 808 White respondents in south London. Results Questionnaires were completed by 327 respondents in Barbados (93% response); 42% men and 58% women, with a mean age of 40.4 years (SD 12.6). The main religious groups were Anglican (29%) and Pentecostal (24%). Educational levels ranged from 18% not completing 5th form to 12% with university education. Attitudes to the notion of organ donation were favourable, with 73% willing to donate their kidneys after their death and only 5% definitely against this. Most preferred an opt-in system of donation. Responses to nine attitudinal questions identified 18% as having no concerns and 9% as having 4 or more concerns. The highest level of concern (43%) was for lack of confidence that medical teams would try as hard to save the life of a person who has agreed to donate organs. There was no significant association between age, gender, education or religion and attitudinal barriers, but greater knowledge of donation had some positive effect on attitudes. Comparison of attitudes to donation in south London and Barbados (adjusting for gender, age, level of education, employment status) indicated that a significantly higher proportion of the south London Caribbean respondents identified attitudinal barriers to donation. Conclusions Community attitudes in Barbados are favourable to deceased donation based on a system of informed consent. Comparison with south London data supports the hypothesis that the relatively high prevalence of negative attitudes to deceased donation among disadvantaged ethnic minorities in high income countries may reflect feelings of marginalisation and lack of belonging.